Advanced Information Systems Engineering Workshops : CAiSE 2019 International Workshops, Rome, Italy, June 3-7, 2019, Proceedings /: CAiSE 2019 International Workshops, Rome, Italy, June 3-7, 2019, Proceedings. ([2019]) - Unknown
No abstract available